(untitled) (Romano-arabica, 2025)
As indicated by the title, this study deals with the phonetic adaptation of the Arabic loanwords in the Dobrujan Tatar. This Turkic variety possesses a large number of Arabic lexical borrowings due to the fact that Arabic is the language of the Quran, a language of high prestige for Muslims. Arabic, as a donor language, is closely related to the spread of the Islamic religion among the Turkic populations. Several phonological processes in Dobrujan Tatar apply with regard to the adaptation of lexical borrowings from Arabic.